Association of Obesity and Luminal Subtypes in Prognosis and Adjuvant Endocrine Treatment Effectiveness Prediction in Chinese Breast Cancer Patients - Tong, Yiwei; Zhu, Siyi; Chen, Weiguo; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2022)
Purpose: To evaluate the influence of obesity on clinicopathological characteristics of breast cancer; to explore the effect of obesity on the prognosis and performance of endocrine therapy in breast cancer patients. Patients and methods: Patients with luminal/HER2-negative early breast cancer were included and categorized into the non-obese (BMI<28kg/m2) and obese (BMI≥28kg/m2) groups according to body mass index (BMI). Clinicopathological characteristics and treatment modalities were compared between groups. Interaction of adjuvant endocrine therapy with obesity was analyzed. Results: A total of 2875 patients were included: 2598 non-obese and 277 obese. A higher rate of patients with comorbidities (OR: 2.83, 95%CI 2.13-3.74, P<0.001) or PR-positive tumor (OR: 1.63, 95%CI 1.03-2.58, P=0.037) were identified in the obese group. Obesity was not associated with disease recurrence (P=0.839) or overall survival (P=0.140) in the whole population. Subgroup analysis did show an association with worse relapse-free survival (RFS, HR 3.48, 95%CI 1.31-9.22, P=0.012) and overall survival (OS, HR 4.67, 95%CI 1.28-16.95, P=0.019) in luminal A breast cancer. These results could not be reproduced in the luminal B subtype with a RFS (HR 0.78, 95%CI 0.41-1.49, P=0.454) or OS (HR 1.17, 95%CI 0.50-2.74, P=0.727). Furthermore, obesity didn’t impact endocrine therapy effectiveness, neither in Tamoxifen nor aromatase inhibitor group (RFS: interact P=0.381; OS: interact P=0.888). Conclusion: The impact of obesity on prognosis interacted with luminal subtype status in Chinese breast cancer patients, which was not related with endocrine treatment modality.